Domain‐Specific and Domain‐General Functional Brain Alterations in Type 2 Diabetes Mellitus: A Task‐Based and Functional Connectivity Meta‐Analysis - Valentino Marcel Tahamata; Yang‐Teng Fan; Li Wei; Yen‐Nung Lin; Roger Marcelo Martinez; Kah Kheng Goh; Yu‐Chun Chen; Chenyi Chen (Brain and Behavior)
ABSTRACT Introduction Patients with Type 2 diabetes experience cognitive and affective deficits linked to widespread functional brain alterations. However, previous meta‐analyses of functional neuroimaging have primarily focused on the resting‐state studies. While valuable, this approach may have overlooked the key neuronal mechanisms underlying these deficits. Methods To address this, we conducted a coordinate‐level task‐based meta‐analysis of functional neuroimaging via a systematic search of Embase, PubMed, Medline, and Web of Science (December 2023), alongside task‐based and task‐free connectivity analyses using the BrainMap database. Activation likelihood estimations were applied to two task categories: that are, cognitive and affective. To control for biased results, we also conducted jackknife sensitivity analysis and within‐paper combined experiments analysis as validation analyses. Results We identified a cluster of activation in cognitive paradigm (18 contrasts, 153 foci, 767 subjects), with the middle frontal gyrus, part of the medial frontal cortex, as the peak region. For the affective paradigm (18 contrasts, 181 foci, 951 subjects), we observed both increased and decreased activities. Two increased clusters peak in the amygdala and middle temporal gyrus, while the three decreased clusters were inferior frontal gyrus, insula, and putamen. Follow‐up connectivity analyses showed that these brain alterations were both task‐specific and task‐generic. Conclusion Despite the lack of uniformity across task, such domain‐specific and domain‐general patterns of alterations provide a more nuanced understanding of the cognitive and affective deficits in Type 2 diabetes patients. This highlights the varied neuronal mechanisms underlying these deficits.